Akulturasi Budaya pada Komunitas Bali Muslim di Desa Pegayaman Buleleng Melalui Kesenian Burdah - Wahyu Surya Ababiel; Putri Ekaresty Haes; Kadek Adyatna Wedananta; Ni Putu Yunita Anggreswari (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2026)
This study aims to analyze and describe the process of cultural acculturation occurring in the Balinese Muslim community in Pegayaman Village, Buleleng Regency, through Burdah art as a means of communication and cultural expression. This phenomenon demonstrates how the Muslim community in Pegayaman is able to combine Islamic values ​​with local Balinese wisdom in traditional art practices. This study uses a qualitative descriptive approach with George Herbert Mead's symbolic interaction theory as the basis of analysis, which focuses on the meaning of symbols and social interactions in shaping cultural identity. Data were obtained through observation, in-depth interviews, and documentation studies of community leaders and Burdah artists. The results show that Burdah art is an important tool in preserving religious identity while unifying cultural differences between the Muslim and Hindu communities in Bali. Acculturation is evident in the blend of Islamic poetry with Balinese rhythms and traditional clothing, which demonstrate harmony, tolerance, and social harmony. These findings prove that traditional art can function as an effective medium of intercultural communication in creating a space for dialogue, maintaining local values, and strengthening the multicultural character of the Pegayaman community.